Multiple Health Risk Behaviors in Young Adult Smokers: Stages of Change and Stability over Time. Issue 2 (3rd June 2019) - Ramo, Danielle E; Thrul, Johannes; Vogel, Erin A; Delucchi, Kevin; Prochaska, Judith J
Abstract : Most young adult smokers engaged in multiple health risk behaviors, in patterns (e.g., substance use behaviors, metabolic risk behaviors) that were largely stable over 12 months. Abstract: Background: Health risk behaviors (HRBs) are common, yet not well understood in young adult smokers. Purpose: We examined HRB profiles over 12 months in young adult smokers participating in a Facebook smoking cessation intervention clinical trial. Methods: Participants ( N = 500; age M = 20.9 years; 54.6% women) were recruited online and randomized to receive either a 3-month Facebook smoking cessation intervention or referral to Smokefree.gov (control). A Health Risk Assessment determined risk for 10 behaviors at baseline and 3, 6, and 12 months. Latent class analysis (LCA) and latent transition analysis (LTA) were used to identify patterns of HRBs and changes over time. Results: At baseline, participants reported an average of 5.4 (standard deviation [ SD ] = 1.7) risk behaviors, including smoking (100%), high-fat diet (84.8%), poor sleep hygiene (71.6%), and low fruit and vegetable intake (69.4%). A 3-class model fit the data best at baseline and all follow-up time points: low risk (28.8% at baseline) with low likelihood of risk on all behaviors except smoking, substance use risk (14.0% at baseline) characterized by heavy episodic drinking, cannabis use, and other illicit drug use, and metabolic risk (57.2% at baseline), with a high percentage of members at risk for a low fruit and vegetable intake, high-fat diet, inactivity, stress, and poor sleep hygiene. Classes were very stable at 3, 6, and 12 months, with few participants transitioning between classes. Conclusions: Most young adult smokers engaged in multiple risk behaviors, with meaningful clustering of behaviors, and demonstrated stability over a year's time. In addition to smoking, targets for intervention are co-occurring substance use and metabolic risk behaviors. Clinical Trials Registration: NCT02207036.